Application of Self-Regulated Approach to Strategic Learning (SRSL) APICPEM on Students’ Learning Achievement in the Topic of Sound Waves - Sari, Ika Mustika; Medellu, Natania Carmenita; Novia, Hera (Journal of Natural Science and Integration, 2024)
Physics is a science that is often considered difficult by students and causes low physics learning achievement. One of the causes of low learning achievement is internal factors that arise from within the students, so a strategy with a self-regulated approach is needed such as the Self-Regulated Approach to Strategic Learning (SRSL) APICPEM (Analyse, Plan, Implement, Comprehend, Problem-Solve, Evaluate, Modify) so that students can carry out learning according to their needs and characteristics. This study aims to determine the application of Self-Regulated Approach to Strategic Learning (SRSL) APICPEM on students’ learning achievement in sound wave material. This research was conducted at a high school in Bandung with a sample of 72 students. The research method used is a mixed method with an unbalanced mixed design (concurrent embedded design). Quantitative data were collected through nonequivalent (posttest only) control group design using the posttest instrument for learning achievement in sound waves. Then qualitative data as a support was collected through narrative qualitative using a SRSL APICPEM mixed questionnaire instrument. The results showed that the implementation of APICPEM SRSL in the experimental group went very good (average score is 80%), with the selection of various student learning strategies according to the characteristics and various other factors, both internal and external factors of students. As well as there is a significant influence from the implementation of SRSL APICPEM on learning achievement with the effectiveness of its influence is evident from the effect size test, which resulted in a value of 0.622, classified as very high. Therefore, this study was able to prove that the application of SRSL APICPEM was able to improve student learning achievement in the topic of sound waves.Keywords: self-regulated, self-regulated approach to strategic learning, learning achievement, sound waves